Pengaruh Corporate Governance terhadap Corporate Social Disclosure pada Sektor Perbankan Konvensional di Indonesia Tahun 2013-2017 - Adnina Fitri Hidayati; Sri suranta (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2018)
This purpose of the research is to examine the effect of Corporate Governance on Corporate Social Disclosure (CSD). GRI G4 is used to measure Corporate Social Disclosure. In this research corporate governance is represented by the size of the board of commissioners, the proportion of independent board of commissioners, and the gender diversity of the board. The sample in this research is all conventional banking in Indonesia through 2013-2017. The sampling technique uses purposive sampling method. The results of multiple linear regression found that the size of the board of commissioners and the proportion of independent commissioners had a positive effect on Corporate Social Disclosure (CSD). While the diversity of board gender and company size (control variable) does not affect Corporate Social Disclosure (CSD).